The relationship between early-onset preeclampsia and the prognostic nutritional index and inflammatory markers - Alev Esercan; Cigdem Cindoglu (Taylor & Francis Group, 2024)
Background Preeclampsia is still a disease whose cause and treatment have not been fully characterised. Early-onset preeclampsia occurs before the 34th week of pregnancy, and late-onset preeclampsia occurs at 34 weeks or older. In our study, we investigated whether the prognostic nutritional index (PNI) and pan immune inflammation value (PIV), which are used in the prognosis and prediction of diseases in new studies in the literature, are useful for predicting early-onset preeclampsia.Methods The first group consisted of healthy pregnant women who had a single foetus without any additional disease between 24 and 34 gestational weeks, and the second group consisted of pregnant women who were diagnosed with early-onset preeclampsia and did not have any additional disease or foetal anomalies during the same gestational week. Neutrophil, lymphocyte, monocyte, thrombocyte, ALB, pan immune inflammation value (PIV) and prognostic nutritional index (PNI) scores were recorded.Results In our case control study, 70 patients with early-onset preeclampsia and 140 pregnant women composed the normotensive (control) group. There was a significant difference between the groups according to PIV (p = 0.04). The prognostic nutritional index (PNI) was significantly lower in the early-onset preeclampsia group than in the normotensive group (p < 0,001). A PNI lower than 36, 30 could only predict early-onset preeclampsia with a low sensitivity of 31.1% and specificity of 45%; the area under the curve was 0,24 (95% confidence interval 0.18-0.31), p < 0,001.Conclusion Patients with PNI scores lower than 36,30 may have early-onset preeclampsia.